Pengaruh Kompetensi dan Kepuasan Kerja terhadap Produktivitas Kerja pada Karyawan Departemen Operasi Pabrik 2 PT Pupuk KALTIM - Kiswanto, Heri; Pertiwi, Pertiwi (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to test and analyze the influence of competence and job satisfaction on work productivity among employees of the Factory Operations Department 2 of PT Pupuk Kaltim Bontang, both partially and simultaneously. The population in this study were all employees in the Factory Operations Department 2 of PT Pupuk Kaltim totaling 134 employees and the sample for this study was 44 employees obtained using the Nonprobability Sampling technique using systematic sampling. Data collection methods use observation, interviews and questionnaires. Data analysis uses descriptive methods, data quality tests, classical assumption tests and multiple linear regression analysis with the help of SPSS 16. The research results show that competency and job satisfaction partially influence work productivity. Simultaneously, competency and job satisfaction have a significant effect on work productivity for employees of Factory Operations Department 2 PT Pupuk Kaltim. The coefficient of determination or R square value is 0.737, from these results all independent variables have a contribution of 73.7% to the dependent variable with a high level of accuracy, and the remaining 26.3% is influenced by other variables that were not included in the research. Keywords: Competence, Job Satisfaction, Factory Operations Department 2 PT Pupuk Kaltim, Work Productivity